Insider and Liquidity Trading in Stock and Options Markets - Biais, Bruno; Hillion, Pierre (Review of Financial Studies, 1994)
We analyze the introduction of a nonredundant option, which completes the markets, and the effects of this on information revelation and risk sharing. The option alters the interaction between liquidity and insider trading. We find that the option mitigates the market breakdown problem created by the combination of market incompleteness and asymmetric information. The introduction of the option has ambiguous consequences on the informational efficiency of the market. On the one hand, by avoiding market breakdown, it enables trades to occur and convey information. On the other hand, the introduction of the option enlarges the set of trading strategies the insider can follow. This can make it more difficult for the market makers to interpret the information content of trades and consequently can reduce the informational efficiency of the market. The introduction of the option also has an ambiguous effect on the profitability of insider trades, which can either increase or decrease depending on parameter values.